Agroforestry Systems Practiced in Kashmir Valley of Jammu and Kashmir - Mughal, A. H.; Bhattacharya, P. K. (Indian Forester, 2002)
Traditional agroforestry systems were identified for the first time in the Kashmir Valley as till date no work was reported from the area in the field. Agroforestry systems identified were boundary plantations, Agri-silviculture, Horti-silviculture, Horti-pasture, Horti-silviagriculture and Kitchen gardens. A broad evaluation of the systems show that only three tree species i.e. Populus deltoides, Salix alba and Robinia pseudoacacia are extensively planted. Adequate representation of all the components is lacking in the systems and in some of the models tree component is far less and utilization of space in these systems is not efficient, besides the yield of agricultural crops is also less. Thus there is a need to make the models viable by the intervention of scientific agroforestry which need to be devised for the areas.